กระบวนการร่างรัฐธรรมนูญแห่งราชอาณาจักรไทยในปีพุทธศักราช 2540 : ปฏิสัมพันธ์เชิงอำนาจระหว่างกลุ่มผลักดัน และชนชั้นนำทางการเมือง - ยอดชาย ชุติกาโม (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The purpose of this study is to study the process of drafting the Thai constitution in 1997 focusing on power interactions between pressure groups and political elites towards the content of the constitution drafted by members of the Constitution Drafting Council. The drafting has gone through various steps including opinion polls and public hearings. It is found that political elites and pressure groups would like to reform politics by having the new constitution drafted. The content of the new constitution tends to be in line with the elites’ opinion more than that of the pressure groups. During the drafting process, conflicts on various issues have occurred between different groups of political elites and members of the Constitution Drafting Council. Such conflicts lead to negotiations and compromises to satisfy such groups of political elites as some members of the House of Representatives and some members of Parliament. Consequently, they would vote for the constitution. The pressure groups, however, do not have any influence on the changes of the content of the constitution. The main issue proposed by the constitution drafting committee is the public hearing process. Although members of the Constitution Drafting Council prioritize this issue, in practice they do not pay much attention to it. It seems that members of the Constitution Drafting Council have drafted the constitution mainly according to their ideologies and will while taking public opinion into consideration a little.